2020
DOI: 10.1002/tqem.21696
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale electricity generation through thermal harvesting in rooftop photovoltaic picogrid using passively cooled heat conversion devices

Abstract: Investigated in this study is harnessing the heat energy absorbed by photovoltaic (PV) solar cells for electricity generation, in order to boost the electric power output of rooftop PV power system, without expending on cooling the energy conversion devices. An experiment was carried out in which a metallic plate was attached to the back of a low rate rooftop PV installation to capture the waste heat of the PV array and evenly distribute the heat to the conversion devices. Four commercial thermoelectric genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Colour change from red to green, of the acid-indicator solution, showed that the liberated ammonia has been trapped and so the green colour solution was then titrated against 0.01N HCl. The colour turning from green to wine at the end point, indicated that all the nitrogen trapped as (NH 4 ) 2 BO 3 has been removed as NH 4 Cl, and the percentage nitrogen of the sample was thus determined while the difference gave the sample's percentage oxygen content.…”
Section: Ultimate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Colour change from red to green, of the acid-indicator solution, showed that the liberated ammonia has been trapped and so the green colour solution was then titrated against 0.01N HCl. The colour turning from green to wine at the end point, indicated that all the nitrogen trapped as (NH 4 ) 2 BO 3 has been removed as NH 4 Cl, and the percentage nitrogen of the sample was thus determined while the difference gave the sample's percentage oxygen content.…”
Section: Ultimate Analysismentioning
confidence: 99%
“…For electric power generation, a promising alternative to the use of conventional fuels has been found in renewable energy technology. Off-grid electrification using electricity generated from non-conventional energy resources, together with installation of stand-alone distribution minigrids, has been adjudged capable of securely delivering electricity for lighting, water supply, telecommunication, irrigation and small-scale commercial purposes, among others [ 3 , 4 , 5 ]. The negative impacts of carbon footprints of fossil fuels on the environment and the possibility of depleting the natural reserve of fossils, are other reasons for Nigeria to tilt towards the clean and replenishable alternative resources for the development of its energy sector [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental and simulation study has been published that investigated the capability of integrating multiple renewable energies such as wave, solar, and wind [119][120][121][122][123][124]. The authors presented a new simulation and analysis approach for integrating an intermittent energy system based on dynamic modelling and control strategy.…”
Section: Emerging Simulation Strategiesmentioning
confidence: 99%
“…Microgrid electrification has been widely studied [ 15 , 16 ] and various replenishable energy resources: solar [ 17 , 18 , 19 , 20 , 21 , 22 ], wind [ 23 , 24 , 25 , 26 ], hydro [ 27 , 28 ], sea wave [ 29 , 30 ], as well as hybrids [ 31 , 32 , 33 , 34 ]; are in use. Electricity generation based on biomass generally and agro-residues in particular is spreading wide among the nations of the world.…”
Section: Introductionmentioning
confidence: 99%